Correction to ‘Genotyping of Malaysian G6PD-deficient neonates by reverse dot blot flow-through hybridisation’ (Journal of Human Genetics, (2020), 65, 3, (263-270), 10.1038/s10038-019-0700-7) - Alina M.F.; Azma R.Z.; Norunaluwar J.; Azlin I.; Darnina A.J.; Cheah F.C.; Noor-Farisah A.R.; Siti-Hawa A.A.; Danny X.R.K.; Zulkifli N.F.; Ainoon O. (Springer Nature, 2024)
Indexed by Scopus/ERA